Diferenciación y conectividad de las ciudadanías con miras a una defensa de la categoría de ciudadanía social global - Solís, Mario (2013)
This paper focuses on the concept of citizenship, particularly in the debate concerning T. H. Marshall’s tripartite conception of citizenship. The paper re-examines Marshall’s notion of social citizenship and defends the thesis that social citizenship may well be invoked at the global level. Drawing on this possibility, the article seeks to put in perspective the tensions between the national and the global.